An Extension of Generalized (ψ, φ)-Weak Contractions. (8th August 2012) - An, Tran Van; Chi, Kieu Phuong; Karapınar, Erdal; Thanh, Tran Duc
Abstract : We prove a fixed-point theorem for a class of maps that satisfy generalized( ψ, φ ) -weak contractions depending on a given function. An example is given to illustrate our extensions.